Overview of "Free Will: An Introduction to Contemporary Theories" by Nedžib Prašević: (Nedžib Prašević, Free Will: An Introduction to Contemporary Theories, Belgrade: Srpsko filozofsko društvo, 2019, 196 pp.) - Nedeljković, Mitar Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
An overview of the book "Free Will: An Introduction to Contemporary Theories" by Nedžib Prašević.
Keywords: free will; determinism; moral responsibility